Structural, Functional, and Metabolic Brain Markers Differentiate Collision versus Contact and Non-Contact Athletes - Churchill, Nathan W.; Hutchison, Michael G.; Di Battista, Alex P.; Graham, Simon J.; Schweizer, Tom A. (Frontiers in Neurology, 2017)
There is growing concern about how participation in contact sports may affect the brain. Retrospective evidence suggests that contact sports are associated with long-term negative health outcomes. However, much of the research to date has focused on former athletes with significant health problems. Less is known about the health of current athletes in contact and collision sports who have not reported significant medical issues. In this cross-sectional study, advanced magnetic resonance imaging (MRI) was used to evaluate multiple aspects of brain physiology in three groups of athletes, participating in non-contact sports (N=20), contact sports (N=22) and collision sports (N=23). Diffusion tensor imaging (DTI) was used to assess white matter microstructure based on measures of fractional anisotropy (FA) and mean diffusivity (MD); resting state functional MRI (fMRI) was used to evaluate global functional connectivity; single-voxel spectroscopy (SVS) was used to compare ratios of neural metabolites, including n-acetyl aspartate (NAA), creatine (Cr), choline (Cho) and myo-insositol (Ins). Multivariate analysis revealed structural, functional and metabolic measures that reliably differentiate between sport groups. Both collision and contact sport groups had significantly elevated FA and reduced MD in white matter, compared to the non-contact group. In contrast, only the collision group showed significant reductions in functional connectivity and the NAA/Cr metabolite ratio, relative to the non-contact group. For brain regions associated with contact sport participation, athletes with a history of concussion also showed greater alterations in FA and functional connectivity, indicating a potential cumulative effect of contact exposure and concussion history on brain physiology. These findings indicate persistent differences in brain physiology for athletes participating in contact and collision sports, which should be considered in future studies of concussion and subconcussive impacts.